Easy to use and reliable technique for online dissolved oxygen tension measurement in shake flasks using infrared fluorescent oxygen-sensitive nanoparticles. Issue 1 (December 2016) - Flitsch, David; Ladner, Tobias; Lukacs, Mihaly; Büchs, Jochen
Abstract Background Despite the progressive miniaturization of bioreactors for screening purposes, shake flasks are still widespread in biotechnological laboratories and industry as cultivation vessels. Shake flasks are often applied as the first or second step in applications such as strain screening or media optimization. Thus, there are ongoing efforts to develop online measurement techniques for shake flasks, to gain as much information as possible about the cultured microbial system. Since dissolved oxygen tension (DOT) is a key experimental parameter, its accurate determination during the course of experiment is critical. Some of the available DOT measurement techniques can lead to erroneous measurements or are very difficult to handle. A reliable and easy to use DOT measurement system, based on suspended oxygen-sensitive nanoparticles, is presented in this work. Results In a cultivation ofKluyveromyces lactis, a new DOT measurement technique via suspended oxygen-sensitive nanoparticles was compared with the conventional DOT measurement via fixed sensor spots. These experiments revealed the main disadvantage of applying sensor spots. With further cultivations ofEscherichia coli andHansenula polymorpha, the new measurement technique was successfully validated. In combination with a RAMOS device, kL a values were determined during the presented cultivations. The determined kL a values are in good agreement with a correlation recently found in the literature. Conclusions The presented DOT measurement technique via suspended oxygen-sensitive nanoparticles in shake flasks turned out to be easy to use, robust and reliable under all applied combinations of shaking frequencies and filling volumes. Its applicability as an online monitoring system for cultivations was shown by means of four examples. Additionally, in combination with a RAMOS device, the possibility of experimental kL a determination was successfully demonstrated.